Evaluating dose-limiting toxicities of MDM2 inhibitors in patients with solid organ and hematologic malignancies: A systematic review of the literature. (November 2019) - Pi, L; Rooprai, J; Allan, DS; Atkins, H; Bredeson, C; Fulcher, AJ; Ito, C; Ramsay, T; Shorr,; Stanford, WL; Sabloff, M; Christou, G
Highlights: Ten inhibitors of MDM2 have been used in 18 studies of adult cancer. Two thirds of studies did not define a dose limiting toxicity a priori. The most common toxicities were cytopenias, GI toxicity and metabolic disturbances. There was one death attributed to treatment with MDM2 inhibitors. MDM2 inhibitors may represent a safe adjuvant therapy for acute leukemia. Abstract: Introduction: Mouse double minute 2 protein (MDM2), a negative regulator of the p53 tumour suppressor gene, is frequently amplified in malignancies. MDM2 antagonists have shown efficacy in treating malignancies with MDM2 overexpression and can overcome chemoresistance in acute myeloid leukemia. We systematically evaluated the safety profile of MDM2 inhibitors in the treatment of solid organ and hematologic malignancies. Materials and Methods: We searched Medline and EMBASE from January 1947 to November 2018 for prospective clinical studies, in English or French, investigating any MDM2 inhibitor in pediatric or adult cancers, and reporting dose and toxicity outcomes. Primary outcome was dose-limiting toxicity (DLT) and secondary outcome was death. Results: The search yielded 493 non-duplicate citations. Eighteen studies of 10 inhibitors met inclusion criteria (total N = 1005 patients). Two-thirds of included studies did not define DLTs and the reporting of toxicities was highly variable. The most commonly reported DLTs were cytopenias, gastrointestinal toxicity, metabolic disturbances, fatigue and cardiovascular toxicity; there was one death attributed to treatment toxicity. Conclusion: MDM2 antagonists have been studied in a variety of malignancies with toxicities similar to other commonly used chemotherapy agents and may represent a safe adjuvant treatment for further study in in acute leukemia.